Modeling and experimental verification of a coupled-tank apparatus - Thet Su Htun. (2008)
In this dissertation, we study the coupled-tank apparatus and develop SIMULINK model, which captures the dynamics of the coupled-tank. We performed the experiments on the coupled-tank in opened-loop to determine the steady state relationship between the input voltages and liquid flow rates of the pumps. Various experimental methods, such as constant and various time intervals were compared.